Her Worship : Hazel McCallion and the development of Mississauga - Urbaniak, Tom, 1976- (University of Toronto Press, 2009)
The first full-length study of McCallion's politics and the development of Mississauga, Her Worship examines the mayor's shrewd pragmatism and calculated populism.